Technology-enacted abusive supervision and its effect on work and family. Issue 3 (4th May 2021) - Valle, Matthew; Carlson, Dawn S.; Carlson, John R.; Zivnuska, Suzanne; Harris, Kenneth J; Harris, Ranida B.
ABSTRACT: This study examines the effects of technology-enacted abusive supervision, defined as subordinate perceptions of supervisor's use of information and communication technologies (ICTs) to engage in hostile communications. This research was designed to examine if technology-enacted abusive supervision has an impact on both the work and family domains. Based on conservation of resources theory, we theorize that technology-enacted abusive supervision enhances subordinate engagement in emotional labor surface acting, which contributes to emotional exhaustion, which in turn impacts both the work and family domains. Results demonstrate significant paths in both domains. Subordinate perceptions of technology-enacted abusive supervision are positively related to the engagement in technology-enacted incivility through the serial mediation of emotional labor surface acting and emotional exhaustion. Additionally, subordinate perceptions of technology-enacted abusive supervision are positively related to family undermining at home for the subordinate through the serial mediation of emotional labor surface acting, emotional exhaustion, and stress transmission.